Attitudes on Policy and Punishment: Opposition to Inequality-Based Government Aid Predicts Support for Capital Punishment - Trahan, Adam; Voss, Andrew S.; Fowler, Shannon K. (International Journal of Criminology and Sociology, 2024)
Objective: There exists a well-developed body of research on the attitudinal correlates of support for capital punishment. Among the most robust of these is racism and racial attributions. The study presented here was designed to explore whether policy prescriptions reflective of racial attitudes can predict support for capital punishment. Method: Data come from the 2018 iteration of the NORC General Social Survey. The dependent variable is a dichotomous measure of support for the death penalty for people convicted of murder. The independent variable is a 5-level Likert-type item of support for government aid to Blacks to help overcome discrimination. Binary logistic regression was used to analyze the relationship between variables net of standard controls. Results: Over 63 percent of the total sample supported the death penalty. Support among those strongly favored government aid to Blacks was 41 percent. Support among those who strongly rejected aid to Blacks was 78 percent. Results of the regression analysis showed each decrease in the level of support for government aid to Blacks was associated with an 18.6 percent increase in the likelihood of supporting the death penalty. Conclusion: Capital punishment support is not simply a function of abstract, hypothetical racial attitudes. The findings reported here suggest support for the death penalty is associated with concrete policy prescriptions that maintain racial inequalities. Given that capital punishment continues in large part due to public support, it should be recognized that this support is based on a desire to maintain racial inequalities through government action.